The effect of modulation on heat transport by a weakly nonlinear thermal instability in the presence of applied magnetic field and internal heating - Manjula, S.H.; Kiran, Palle; Narsimlu, Gitti; Roslan, Rozaini (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with a weakly nonlinear stability problem under an imposed time-periodic thermal modulation. The temperature has two parts: a constant part and an externally imposed time-dependent part. We focus on stationary convection using the slow time scale and quantify convective amplitude through the real Ginzburg-Landau equation (GLE).
Keywords: Ginzburg-Landau equation; temperature modulation; applied magnetic field; internal heating